Esophageal Impedance-pH Monitoring and Pharyngeal pH Monitoring in the Diagnosis of Extraesophageal Reflux in Children - Anna Plocek; Beata Gębora-Kowalska; Jakub Białek; Wojciech Fendler; Ewa Toporowska-Kowalska (Gastroenterology Research and Practice)
Various clinical symptoms are attributed to extraesophageal reflux disease (EERD). Multichannel intraluminal impedance-pH monitoring (MII-pH) is considered to correlate symptoms with acid and nonacid gastroesophageal reflux (GER) events. Pharyngeal pH monitoring (Dx-pH) is considered to correlate the decrease in the pH level in the oropharynx with reported symptoms and to diagnose supraesophageal reflux. We aimed to assess the correlation between acid reflux episodes recorded by Dx-pH and GER detected via MII-pH in children with suspected EERD. The study enrolled 23 consecutive children (15 boys and 8 girls; median age 8.25 [range 3-16.5] years) with suspected EERD. MII-pH and Dx-pH were conducted concurrently in all patients. A total of 1228 reflux episodes were recorded by MII-pH. With the antimonic sensor placed inside the impedance probe, 1272 pH-only reflux episodes were recorded. Of these, 977 (76.81%) were associated with a retrograde bolus transit. Regarding GER, 630 full-column episodes extended to the most proximal pair of impedance sensors; 500 (83.33%) demonstrated an acidic character. The following acid reflux numbers were determined by the Dx-pH system: for pH<4, n=126; pH<4.5, n=136; pH<5, n=167; and pH<5.5, n=304, and for a decrease in pH>10% relative to the baseline, n=324. There was no significant correlation between the number of pharyngeal reflux episodes detected by Dx-pH and that of GERs identified by MII-pH. The proportion of oropharyngeal pH events that were temporally related to a GER episode increased with the extended pH criteria. The highest proportion was observed for a pH decrease of ≥10% from the baseline and did not exceed 5.2%. The application of the extended pH criteria in the Dx-pH system resulted in an increase in the number of diagnosed laryngopharyngeal refluxes; most were not temporally associated with GER episodes confirmed by MII-pH. Thus, the efficacy of the exclusive application of Dx-pH for supraesophageal gastric reflux diagnosis is uncertain.